1980
DOI: 10.1111/j.1399-6576.1980.tb01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Hemodynamic Effect of Pharmacological Doses of Methylprednisolone in Dogs, and the Influence of Speed of Injection

Abstract: Reports of sudden death of patients during i.v. administration of methylprednisolone (M.P.) prompted the present study of the hemodynamic effect of M.P. given i.v. to dogs. Fifteen healthy, mongrel dogs were anesthetized with thiomebumal, fentanyl, droperidol, pancuronium and N2O/O2. With ventilation and circulation in steady state, M.P. 30 mg/kg b.w. was given i.v. either as a push bolus (n=7) or over a 5-min period (n=8). In the bolus group, mean aortic pressure (MAP) and systemic vascular resistance (SVR) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Husum et al 44 performed a similar study in dogs and confirmed that rapid bolus administration can cause a drop in systemic vascular resistance, hypotension, and a decrease in ionized calcium. Certain patients may be intolerant of these circulatory changes.…”
Section: Mechanism Of Reactionmentioning
confidence: 82%
“…Husum et al 44 performed a similar study in dogs and confirmed that rapid bolus administration can cause a drop in systemic vascular resistance, hypotension, and a decrease in ionized calcium. Certain patients may be intolerant of these circulatory changes.…”
Section: Mechanism Of Reactionmentioning
confidence: 82%
“…Erstad [37] noted that patients who had adverse cardiovascular reactions to corticosteroids had received individual doses of at least 250 mg of methylprednisolone or its equivalent, usually administered over a short period of time (30 minutes or less). A study in dogs found that a rapid infusion of high-dose methylprednisolone resulted in a decrease in systemic vascular resistance, mean aortic pressure, and ionized calcium [38], all of which could lead to cardiovascular collapse. The proposed mechanism for the observed findings was an α-adrenergic blockade and a direct negative effect of the steroid on the myocardium.…”
Section: Pathophysiologymentioning
confidence: 98%
“…In these cases, inhibition of cyclooxygenase is suggested to cause bronchospasm by blocking prostaglandin production which results in increased leukotriene production [30,31]. Others suggested that some of these reactions, such as cardiovascular collapse, can be explained by rapid infusion of a considerable amount of corticosteroids, causing a decrease in cardiac output, secondary to α-adrenergic blockade and a negative inotropic effect [32,33]. …”
Section: Discussionmentioning
confidence: 99%